2016
DOI: 10.1108/cms-10-2015-0240
|View full text |Cite
|
Sign up to set email alerts
|

Differential leadership, team conflict and new product development performance

Abstract: Purpose The purpose of this paper is to investigate the impact of native Chinese R&D team directors’ differential leadership on team performance, so as to understand whether and how the directors’ differential leadership impacts team conflict, whether and how team conflict impacts new product development performance of the R&D team and whether team conflict plays full mediation on the relationship between directors’ differential leadership and new product development performance. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Authoritarian leadership represents strong authority and demands unquestioned obedience from subordinates (Farh and Cheng, 2000). Differential leadership refers to leaders distinguishing the subordinates as the in-groups or out-groups (Zhou et al , 2016). Many studies using Chinese sample have indicated that authoritarian leadership and differential leadership have negative outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authoritarian leadership represents strong authority and demands unquestioned obedience from subordinates (Farh and Cheng, 2000). Differential leadership refers to leaders distinguishing the subordinates as the in-groups or out-groups (Zhou et al , 2016). Many studies using Chinese sample have indicated that authoritarian leadership and differential leadership have negative outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using Chinese sample have indicated that authoritarian leadership and differential leadership have negative outcomes (e.g. Zhou et al , 2016). As the opposite of authoritarian leadership and differential leadership, our study demonstrated that moderate inclusive leadership is good for groups, which is consistent with research concerning authoritarian leadership and differential leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Differential leadership was proposed by Cheng (1995), which originated from Fei Xiaotong's Chaxugeju (Fei et al, 1992), a differential pattern that Chinese people treat others depending on the distance of their self-centered circle (Zhou et al, 2016). Cheng (1995) and Hu et al (2004) applied the differential mode of Chinese social relationship to the organizational context and found that the leaders display favoritism toward the in-group members rather than the out-group members in Chinese organizations.…”
Section: Differential Leadership and Organizational Corruptionmentioning
confidence: 99%
“…Zhou et al . (2016) together investigated the implications of differential treatments by the Director of R&D (Research & Development).…”
Section: Overview and Papersmentioning
confidence: 99%